Blocking migration of regulatory T cells to leukemic hematopoietic microenvironment delays disease progression in mouse leukemia model. (28th January 2020) - Wang, Rong; Feng, Wenli; Wang, Hao; Wang, Lina; Yang, Xiao; Yang, Feifei; Zhang, Yingchi; Liu, Xiaoli; Zhang, Dongyue; Ren, Qian; Feng, Xiaoming; Zheng, Guoguang
Abstract: Blocking the migration of regulatory T cells (Tregs) to the tumor microenvironment is a promising strategy for tumor immunotherapy. Treg accumulation in the leukemic hematopoietic microenvironment (LHME) has adverse impacts on patient outcomes. The mechanism and effective methods of disrupting Treg accumulation in the LHME have not been well established. Here, we studied the distribution and characteristics of Tregs in the LHME, investigated the effects of Treg ablation on leukemia progression, explored the mechanisms leading to Treg accumulation, and studied whether blocking Treg migration to the LHME delayed leukemia progression in MLL-AF9-induced mouse acute myeloid leukemia (AML) models using wildtype (WT) and Foxp3 DTR/GFP mice. Increased accumulation of more activated Tregs was detected in the LHME. Inducible Treg ablation prolonged the survival of AML mice by promoting the antileukemic effects of CD8 + T cells. Furthermore, both local expansion and migration accounted for Treg accumulation in the LHME. Moreover, blocking the CCL3-CCR1/CCR5 and CXCL12-CXCR4 axes inhibited Treg accumulation in the LHME and delayed leukemia progression. Our findings provide laboratory evidence for a potential leukemia immunotherapy by blocking the migration of Tregs. Graphical abstract: Image 1 Highlights: More activated Tregs with elevated immunosuppressive activity accumulate in leukemic hematopoietic microenvironment. Disrupting Treg accumulation in LHME enhances the anti-leukemic effects of CD8 + T cells. Local expansion and increased migration contribute to Treg accumulation in leukemic hematopoietic microenvironment. Blocking CCL3-CCR1/CCR5 and CXCL12-CXCR4 axes decreases Treg accumulation in leukemic hematopoietic microenvironment.